ΣN Strong Interactions - Johnstone, John A. (My University, 1979)
The availability Σ¯ atomic and ΣN scattering data are fitted consistently within a finite range potential model.
The most recent analysis of ΣN scattering data produced two possible sets of complex scattering lengths consistent with the observed cross-sections. These data, together with measured energy level shifts and widths in Σ¯atoms, are analyzed to determine if the combined data are consistent and also to extract effective Σ¯N potentials.
The calculations are performed by assuming Yukawa-shaped complex potentials for each Σ¯ spin, isospin channel. These potentials are then folded into the nuclear density distribution to produce the Σ¯ nucleus effective potential and the Schrödinger equation solved for the level widths and shifts. The potential depths and range are treated as parameters which are varied to minimize the total x² of the fit to the scattering lengths and atomic data. The possibilities of attractive or repulsive potentials are examined for those Σ¯N channels which produce positive scattering lengths.
Although the results of this analysis indicate that the atomic data can be fitted consistently with the scattering data, there is no conclusive distinction between the two sets of scattering lengths in this respect.
It is concluded however that the existence of a Σ¯n bound state is unlikely and that the Σ¯ spin triplet potential at least must be repulsive.
Keywords: Physics; Physics